UPAYA MENINGKATKAN USAHA TENUN SONGKET TRADISIONAL LOMBOK MELALUI PEMBERDAYAAN PENENUN (STUDI KASUS PADA UD. UNDUR PASANG) - Baiq Herdina Septika; Sri Sukarni (SANGKAREANG, 2019)
This study aimed to know the effort of Songket weaving business through empowerment of human resources at UD Undur Pasang.Method of the study was descriptive quantitative. There were 15 weavers taken as samples.Technique for collecting data used interview and questionnaires.In the preliminary study found that empowerment on human resources in UD. Undur Pasang is needed. Based on the result of the study showed that there are two kinds of training needed for empowerment of Human Resources. 1) Communication Training both in Indonesian and English. This training becomes one of the facilities for marketing Lombok Songket weaving product by UD.Undur Pasang. 2) Business management training so that business management becomes better and systematic